KARAKTERISTIK HABITAT DAN PERSEBARAN RHIZANTHES LOWEII. (BECC) HARM DI TAMAN NASIONAL KERINCI SEBLAT RESORT SUNGAI LAMBAI - Ade Ilham; Defri Yoza; Yossi Oktorini (Ensiklopedia of Journal, 2022)
Indonesia is known as one of the countries with the largest biodiversity in the world (megadiversity) and is the center of world biodiversity (megacenter of biodiversity). Rhizanthes loweii has a geographic distribution from Sumatra, Peninsular Malaysia, and Kalimantan. In Sumatra this species has been recorded to be found in Mount Leuser, Sibolangit, Mount Dempo, South Sumatra, Penanggungan, Lampung and Bengkulu. KSNP as one of the largest conservation areas in Indonesia has a very high and diverse potential for natural resources and environmental services. TNKS also has various data objects of natural tourist attractions that have the potential to be developed, including mountains, hills, lakes and waterfalls. This research was conducted in the Kerici Seblat National Park (TNKS) Resort Sungai Lambai. The method that will be used in collecting data in this research is the path method and the determination of the observation plot is carried out by purposive sampling. Each 1 ha measuring plot counted the number of individuals with Rhizanthes loweii buds/flowers. This Important Value Index (INP) is used to determine the species composition and dominance of a species in a stand. Sungai Lambai Resort is located in Nagari Lubuak Gadang Selatan, Sangir District, South Solok Regency, West Sumatra. Nagari Lubuak Gadang Selatan is divided into five jorongs, namely, Jorong Pincuran Tujuh, Jorong Sungai Lambai, Jorong Karang Putiah, Jorong Ayia Manyuruak and Jorong Liki. The vegetation around Rhizanthes loweii contained in the research plot amounted to 32 species with seedling, sapling, pole and tree levels. The soil in this research location is generally alkaline soil. The type of clay soil is dusty, has a smooth texture, and is blackish brown in color. Habitat characteristics and distribution of Rhizanthes loweii in Kerinci Seblat National Park lives on dusty clay soil with blackish brown color and average soil pH of 7.1 (neutral). The average temperature is 23.7⁰ C and the average humidity is 80%.Keywords:  TNKS, Habitat, Distribution, Rhizanthes loweii. (Becc)